Novelties and nomenclatural notes in Pabstiella (Orchidaceae) from the Brazilian Atlantic Rainforest of Bahia and Espírito Santo - Morales, Nicolás Gutiérrez [UNESP]; Toscano De Brito, A. L.V.; Smidt, Eric De Camargo [UNESP] (Magnolia Press, 2023)
Three new species of Pabstiella from Espírito Santo and Bahia in Brazil are described and illustrated, with digital plates, comparative figures, and annotations on their ecology provided. The species are compared with similar taxa, and their phylogenetic placement is hypothesized based on their morphology. In addition, five species are proposed as synonyms, P. teschiana and P. henrique-aragonii as synonyms of P. crenata, P. wanderbildtiana as synonym of P. aurantiaca, P. osculator as synonym of P. rhombilabia and P. menegattii as synonym of P. decurva. A respective taxonomic discussion is provided for each case, and a lectotype is selected for P. aurantiaca.
Keywords: Atlantic Rainforest; Endemism; Monocots; Nomenclature; Taxonomy